A Conceptual Framework for Evidence‐Based Leadership Development Practices. Issue 168 (30th November 2020) - Soria, Krista M.; Johnson, Matthew R.
Abstract: In this chapter, the authors synthesize research on existing leadership development programs and practices, highlight why some practices are more effective in students' leadership development than others, draw theoretical connections between the most influential practices and students' leadership development, and offer a broad conceptual framework about evidence‐based practices for students' leadership development.